Disparities in Criminal Justice System Responses to First-Time Juvenile Offenders According to Indigenous Status - Papalia, Nina (Criminal justice and behavior, 2019)
This study explored the intersection between Indigenous status, gender, and age in relation to law enforcement responses to offending in 53,632 first-time juvenile offenders in Australia. Findings demonstrated that Indigenous offenders were more likely to receive a court summons (rather than diversionary alternative) following their first offense compared with non-Indigenous offenders when controlling for gender, age, and the nature and number of charges processed at first offense. No interactions were observed between Indigenous status, age, and gender. Indigenous status predicted receiving a court summons; however, the strength of this relationship diminished when offenders had one-to-two violent charges and when offenders’ first contact occurred after the commencement of the Young Offenders Act 1997 (NSW), which formalized police responses to diversion. Stronger efforts are needed to prevent initial justice system contact and formal processing among Indigenous youth with a focus on community-led early intervention strategies.